Health Psychology: A Holistic View of the Human Health - Cuevas, Marilis (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2014)
Health, as defined by the World Health Organization is a complete state of physical, mental, and social well-being and not only the absence of diseases. Different controversial models exist to explain the heath-disease debate, which traditionally emerged from the Medicine and Biology fields. Recently the literature proposes the integration from the perspective of the Health Psychology standpoint. This article will present some academic debates from the historically dominant models and their relation and responses to the different perspectives within their contexts. Health Psychology is presented emerges from the theoretical debates in which a diversity of specializations to promote a holistic view of human health. It will also provide an area of opportunities in the fields of psychology profession. With the purpose of enhancing the importance of the factors that intervene with prevention, treatment, and rehabilitation of health issues.